Biomechanical loading of the hip during side jumps by soccer goalkeepers - Schmitt, K. U.; Schlittler, M.; Boesiger, P. (Journal of Sports Sciences, 2010)
There is a risk of hip injury in dives to the side by soccer goalkeepers. In this study, we assessed hip loading in goalkeepers when performing such dives. The experiments were conducted in a laboratory setting using an in-ground force plate as well as on a grass surface when the athletes were equipped with force sensors. The forces acting on the hip were measured and high-speed video analysis was performed, allowing the investigation of the dive characteristics and techniques. The peak force values recorded in the laboratory setting ranged from 3 to 8 kN, which corresponded to 4.2-8.6 times body weight. The vertical impact velocities reached 3.25 m/s. In the field experiments, a hip loading of 87-183 N/cm2 was determined. We found that goalkeepers who perform a rolling motion reduce their hip loading. The data provided by this study add to the biomechanics database and contribute to the establishment of injury criteria. Such information is necessary to develop and implement strategies to help prevent hip injuries.